Assessment of the stability of catechin-enriched extracts obtained from Arbutus unedo L. fruits: Kinetic mathematical modeling of pH and temperature properties on powder and solution systems - Albuquerque, Bianca R. (2018)
B.V. Arbutus unedo L. (strawberry-tree) fruits could be considered an alternative source of flavan-3-ols, in particular catechin and its derivatives. These compounds are known for a variety of applications in food (especially as food additives), pharmaceutical and cosmetic industry. Therefore, catechin-enriched extracts (60% flavan-3-ols and 22% of catechin) were obtained from A. unedo fruits and further submitted to physical and chemical stability studies, considering the main affecting variables (time, temperature and pH): i) a stability study of the extracts during the obtaining and storage procedures (powder system); and ii) a stability study of the extracts in simulated food environment (aqueous solution system). The measured responses were the flavan-3-ols and catechin contents, determined by High performance liquid chromatography couple to a diode array detector (HPLC-DAD), and the antioxidant activity of the extracts evaluated by hydrophilic assays. Mechanistic and phenomenological equations were used to describe the responses, and the optimal conditions for flavan-3-ols (including catechin) stability as powder extract during a month were pH = 5.4 and T = -20 °C; while its stability in aqueous solution remained during the 24 h of application at pH < 4 and T < 30 °C. These results provide useful information for: i) potential industrial use of A. unedo fruits as alternative sources of flavan-3-ols; and ii) shelf-life calculations and catechin loss predictions at specific conditions of temperature and pH. Finally, the results obtained showed a certain agreement with previous reports of catechin stability studies in powder and solution systems, but providing a new alternative source: A. unedo fruits.